Pembelajaran Jigsaw Berbasis Catur Paramitha Untuk Menguatkan Sikap Prososial Siswa Sekolah Dasar - I Made Edi Suta Wiguna; Ni Nyoman Lisna Handayani; I Made Ariasa Giri (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study aimed to examine the effect of the Catur Paramitha-based Jigsaw cooperative learning model on strengthening the prosocial attitudes of fifth-grade students in Cluster III Elementary Schools, Kubutambahan District. A quantitative approach with a quasi-experimental design was employed involving 60 students, consisting of 30 students in the experimental group and 30 students in the control group. Data were collected using a prosocial attitude questionnaire covering empathy, cooperation, social concern, tolerance, and helping behavior, and analyzed using descriptive statistics and an independent-samples t-test. The results showed that the experimental group's mean score increased from 68.43 in the pretest to 84.27 in the posttest, while the control group's score increased from 67.87 to 72.13. Hypothesis testing yielded t = 7.84, p = 0.000 (p < 0.05), with a Cohen’s d effect size of 2.03, indicating a very large effect. These findings demonstrate that integrating the values of Maitri, Karuna, Mudita, and Upeksa into the Jigsaw learning model effectively strengthens students’ prosocial attitudes. Therefore, this model can serve as a local wisdom-based learning strategy to support character education in elementary schools.